2020
DOI: 10.1002/eng2.12101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of winglet geometry on horizontal axis wind turbine performance

Abstract: Winglets (WLs) have recently been used to improve the performance of horizontal axis wind turbine (HAWT). The WL geometry is a key parameter for diverging blade tip vortices away from turbine blades and reducing induced drag. The present study focuses on the effect of winglet height (H) and toe angle ( w ) on the turbine performance. The performance of a three-bladed rotor of 1 m diameter with SD8000 aerofoil is numerically investigated using ANSYS 17.2 CFD on a polyhedral mesh. The model is hence validated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…1. Many works (Hansen and Mühle, 2018;Khalafallah et al, 2019;Khaled et al, 2019;Mourad et al, 2020;Papadopoulos et al, 2020;Aju et al, 2020) are focusing on smaller turbines whereas only three other works (Kalken and Ceyhan, 2017;Matheswaran et al, 2019;Zahle et al, 2018) focus on larger MW turbines as is the case in the present study. Furthermore, as will be evident in Sections 2.2-2.3 there are few available actual optimizations whereas the majority of works are parametric studies and thus better performing tips could very likely be found in the vicinity of the selected parameter settings for these rotor configurations.…”
Section: Literature Reviewmentioning
confidence: 71%
See 3 more Smart Citations
“…1. Many works (Hansen and Mühle, 2018;Khalafallah et al, 2019;Khaled et al, 2019;Mourad et al, 2020;Papadopoulos et al, 2020;Aju et al, 2020) are focusing on smaller turbines whereas only three other works (Kalken and Ceyhan, 2017;Matheswaran et al, 2019;Zahle et al, 2018) focus on larger MW turbines as is the case in the present study. Furthermore, as will be evident in Sections 2.2-2.3 there are few available actual optimizations whereas the majority of works are parametric studies and thus better performing tips could very likely be found in the vicinity of the selected parameter settings for these rotor configurations.…”
Section: Literature Reviewmentioning
confidence: 71%
“…They find that both winglet length and cant angle are amongst the most important design variables for improving performance. Mourad et al (2020) use an initial literature survey covering 10 references to conclude that i) there is no agreement on optimum winglet configuration, ii) height is the most effective winglet parameter, and iii) that upstream directed winglet should be preferred over downstream configurations. Since they found no study covering toe angle, i.e., the angle of attack between tangential velocity component and winglet profile, they carry out a parameter study using height and toe angle as their two parameters.…”
Section: Parametric Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that an optimized winglet design can improve the energy extraction as well as accelerate the recovery of turbulent kinetic energy in the wake by quicker tip vortex interaction. Mourad et al [31] computationally explored the effects of winglet geometry on horizontal axis wind turbines. They found that downwind winglets with toe angles from 10 ○ to 30 ○ can reduce power outputs compared to rotors with no winglets.…”
Section: Introductionmentioning
confidence: 99%